CLIP Tool Kit (CTK): a flexible and robust pipeline to analyze CLIP sequencing data - Shah, Ankeeta (Bioinformatics, 2017)
SUMMARY: UV cross-linking and immunoprecipitation (CLIP), followed by high-throughput sequencing, is a powerful biochemical assay that maps in vivo protein-RNA interactions on a genome-wide scale. The CLIP Tool Kit (CTK) aims at providing a set of tools for flexible, streamlined and comprehensive CLIP data analysis. This software package extends the scope of our original CIMS package. AVAILABILITY AND IMPLEMENTATION: The software is implemented in Perl. The source code and detailed documentation are available at http://zhanglab.c2b2.columbia.edu/index.php/CTK.